2023
DOI: 10.14218/jcth.2022.00362
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicobacter pylori Infection on the Pathogenesis and Management of Nonalcoholic Fatty Liver Disease

Abstract: Helicobacter pylori (H. pylori) infection is widely prevalent worldwide. H. pylori

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…That said, the scenario may be more intricate since some intervention studies suggested that H. pylori eradication therapies could exert some beneficial effects on insulin resistance, serum liver enzymes and other surrogate markers of MASLD. 25,68 With this caveat in mind, we believe that the results of the eligible retrospective Asian cohort studies reporting a significant association between H. pylori infection and the risk of developing incident MASLD should be interpreted cautiously due to the retrospective design of the studies. Furthermore, some of these Asian cohort studies included patients with different H. pylori eradication status at the baseline, and most importantly, no detailed information was available in these cohort studies on the use of H. pylori eradication therapies over the follow-up.…”
Section: Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, the scenario may be more intricate since some intervention studies suggested that H. pylori eradication therapies could exert some beneficial effects on insulin resistance, serum liver enzymes and other surrogate markers of MASLD. 25,68 With this caveat in mind, we believe that the results of the eligible retrospective Asian cohort studies reporting a significant association between H. pylori infection and the risk of developing incident MASLD should be interpreted cautiously due to the retrospective design of the studies. Furthermore, some of these Asian cohort studies included patients with different H. pylori eradication status at the baseline, and most importantly, no detailed information was available in these cohort studies on the use of H. pylori eradication therapies over the follow-up.…”
Section: Weightmentioning
confidence: 99%
“…68,70,71 Recent studies have shown that H. pylori infection may promote the development and progression of MASLD, possibly through several mechanisms, such as low-grade inflammation, increased oxidative stress, insulin resistance and alterations of gut permeability. 68 In particular, low-grade chronic inflammation in the gastric mucosa may exacerbate and promote the local and systemic release of several proinflammatory cytokines, thereby exacerbating systemic insulin resistance, increasing gut permeability and altering the gut microbiome composition. 68 H. pylori infection may alter Bacteroidetes, Lactobacillus, Proteobacteria, Firmicutes and Actinobacteria colonies, thus changing the gut microbiota composition like that observed in obese patients.…”
Section: Weightmentioning
confidence: 99%
“…H. pylori infection can impact the composition and function of the gut microbiota, insulin resistance, and systemic inflammation. [156] Regarding the gut microbiota, H. pylori infection can affect its composition and diversity, potentially influencing the development of MAFLD. However, the precise mechanisms underlying this relationship are not yet fully understood.…”
Section: The Role Of Helicobacter Pylori In the Pathogenesis And Mana...mentioning
confidence: 99%
“…However, the precise mechanisms underlying this relationship are not yet fully understood. Moreover, the systemic inflammatory state that contributes to the pathogenesis of MAFLD is associated with an H. pylori infection, during which the concentration of pro-inflammatory markers increases, potentially influencing the development of MAFLD in a yet-unclear manner [156].…”
Section: The Role Of Helicobacter Pylori In the Pathogenesis And Mana...mentioning
confidence: 99%
“…Additionally, H. pylori -derived products can penetrate the underlying mucosa, triggering both non-specific and specific immune responses in the host [ 3 ]. The literature also implicated this gastric pathogen in the development of extra-digestive diseases, such as atherosclerosis (AS) [ 4 ], chronic obstructive pulmonary disease (COPD) [ 5 ], nonalcoholic fatty liver disease (NAFLD) [ 6 ], blood diseases (idiopathic thrombocytopenic purpura, iron deficiency anemia) [ 7 ], inflammatory bowel disease (IBD) [ 8 ], skin diseases [ 9 ], and Alzheimer's disease (AD) [ 10 ]. Although infection with H. pylori has been shown to cause leaky bowel by impairing the tight-junctional proteins occludin, claudin-4, and claudin-5, there is little evidence of H. pylori in the blood [ 11 ].…”
Section: Introductionmentioning
confidence: 99%